Effect of different herbicides alone and in combination on complex weed flora at early and late stages of direct seeded Basmati rice (Oryza sativa L.) - Bajiya, Rohitash; Bir, Dharam; Punia, S.S.; Yadav, Ashok; Yadav, J.P. (Annals of Agricultural Research, 2016)
A field experiment was carried out during the kharif season of 2013 at Chaudhary Charan SinghHaryana Agricultural University, Regional Research Station, Karnal, India to evaluate the effectof different herbicides as alone and tank-mix on the dynamic and complex weed flora in directseeded Basmati rice. The experimental field was predominantly infested with Echinochloa crusgalli,Eragrostis tenella, Dactyloctenium aegyptium, Ammannia baccifera and Cyperus rotundus.Pendimethalin 1000 g ha–1 (Pre-emergance) fb tank-mix combination of bispyribac-sodium 25 g ha–1 with pyrazosulfuron 25 g ha–1 or azimsulfuron 20 g ha–1 or ethoxysulfuron 18.0-37.5 g ha–1were realized to be the best herbicidal combinations for control of complex weed flora in directseeded rice, with significant improvement in grain yield (4.05-4.10 t ha–1), net returns (1,08,856-1,13,485 ha–1) and B-C ratio (2.45-2.53) as compared to weedy check.